PENINGKATAN KETERAMPILAN MAHASISWA MELALUI PENGOPERASIAN PROGRAM AUTOCAD - Darsini, Darsini; Suprapto, Suprapto (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2021)
Autocad is an application that supports image creation in the engineering design field. This application is able to design technical drawings, plans, buildings and other objects. The problem is, how can we skillfully utilize the facilities provided by Autocad, so that it can make a significant advantage compared to manual drawing. The objectives of the science and technology application program are (1) To provide knowledge and skills about image processing programs (2) To improve student skills in completing image tasks using the Autocad program. The method used in the science and technology application program is the provision of theory and hands-on practice as outlined in the training module. In addition, drawing exercises were also carried out during the activity. The evaluation of the science and technology application activity program about improving the skills of Univet students through the operation of the autocad program is that training in the operation of the autocad program can provide knowledge and skills in students in completing drawing tasks given by lecturers and changes in student competencies (knowledge and skills). in using the computer. This is evident from the average results of drawing exercises and the final grades carried out by the students participating in the training by 75%, previously students were still unfamiliar with operating the autocad program.